3
$\begingroup$

I want to show that for large $n$ the $n$-th prime grows like $n\ln (n)$. Is this correct?

By PNT $$\mathop {\lim }\limits_{x \to \infty } \frac{{\pi (x)\ln (x)}}{x} = 1.$$ Let $x = {p_n}$, so that $\pi (x) = n$, where ${p_n}$ is the $n$-th prime, then $$\mathop {\lim }\limits_{n \to \infty } \frac{{n\ln (n)}}{{{p_n}}} = 1$$ or $${p_n} \sim n\ln (n).$$

$\endgroup$
  • 2
    $\begingroup$ How do you go from the expression in terms of $x$ to the expression in terms of $n$? $\ln(x)$ and $\ln(n)$ aren't interchangeable, for one. The result is correct (roughly), but your derivation isn't... $\endgroup$ – Steven Stadnicki Oct 2 '12 at 0:56
  • $\begingroup$ I knew there was a mistake. $\endgroup$ – glebovg Oct 2 '12 at 0:59
  • $\begingroup$ I think it's assumed that p_n < x < p_(n+1). This is exactly how Apostol begins his proof on p. 80-81. $\endgroup$ – daniel Oct 2 '12 at 1:07
  • $\begingroup$ I think taking the logarithm of ${\lim _{x \to \infty }}\pi (x)\ln (x)/x$, simplifying and multiplying by ${\lim _{x \to \infty }}\pi (x)\ln (x)/x$ yields ${\lim _{n \to \infty }}n\ln (n)/{p_n}$. $\endgroup$ – glebovg Oct 2 '12 at 1:11
4
$\begingroup$

To complete your argument you have to show that $\ln(p_n)/\ln(n) = 1.$

Now, if you have that $p_n \sim n\ln (n),$ then $\ln(p_n) = \ln(n) + \ln\ln(n) + o(1)$, and so indeed $\ln(p_n)/\ln(n) \to 1$ as $n \to \infty$. So at least this is consistent with what you are trying to prove.

On the other other hand, what you know is that $n\ln(p_n)/p_n \to 1$ as $n \to \infty$. Taking $\ln$ gives $$\ln(n) + \ln\ln(p_n) = \ln(p_n) + o(1),$$ and so $$\ln(n)/\ln(p_n) + \ln\ln(p_n)/\ln(p_n) = 1 + o(1).$$ Can you finish from there?

$\endgroup$
  • $\begingroup$ Thanks. I had a similar argument in mind. $\endgroup$ – glebovg Oct 2 '12 at 1:20
2
$\begingroup$

There is a problem with this approach. You took $x = p_n$, but that means $\ln(x) = \ln(p_n)$ and not $\ln(n)$.

$\endgroup$
  • $\begingroup$ Any ideas on how to prove ${p_n} \sim n\ln (n)$ using PNT? $\endgroup$ – glebovg Oct 2 '12 at 1:04
2
$\begingroup$

Assume $(1):\hspace{3mm}\frac{\pi(x) \log x}{x}\sim 1 $, take logs of both sides:

$\lim_{x \to \infty}(\log \pi(x)+ \log\log x - \log x) = 0$

or $$ \lim_{n \to \infty} [ \log x(\frac{\log \pi(x)}{\log x} + \frac{\log\log x}{\log x} -1)] = 0$$

Because $\log x \to \infty$ as $ x \to \infty,$

$$\lim (\frac{\log \pi(x)}{\log x} + \frac{\log\log x}{\log x} -1) = 0 $$

So $$(2) \hspace{3mm}\lim_{x\to\infty} \frac{\log \pi(x)}{\log x} = 1$$ and from (1) we have

$$(3)\hspace{3mm}\lim \frac{\pi(x) \log \pi(x)}{x} = 1 $$ and if $x = p_n, \pi(x) = n, $ so $\pi(x) \log \pi(x) = n \log n$, so (3) implies that

$$\lim_{n\to \infty }\frac{n \log n}{p_n } = 1. $$

This is basically Apostol's proof.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.